Citizen Participation in The Field of Social Welfare Through PKH (Study of Community Empowerment by The Social Service of Nagekeo Regency, East Nusa Tenggara Province) - Maria Yosefina Dadi; Karim Suryadi (Journal of International Conference Proceedings (JICP), 2020)
This article provides and overview of citizen participation in the field of social welfare through the Famili of Hope Program or Program Keluarga Harapan (PKH) to make citizens a good citizen in the context of citizenship education. This research uses a qualitative approach with the case study method. The result of this study indicate that citizen participation in the field of social welfare is carried out by attending Family Ability Improvement Meetings or Pertemuan Peningkatan Kemampuan Keluarga (P2K2), building latrines with a social welfare system between PKH recipients, attending the Family Planning-Integrated Health Service or Pos Pelayanan Keluarga Berencana Kesehatan Terpadu (POSYANDU) for pregnant woman, toddlers and the elderly routinely every month, fulfilment of children’s nutrition, sending their children to school, and joining the Joint Business Group or Kelompok Usaha Bersama (KUBE) consisting of KUBE weaving, agriculture and livestock. With the participation of citizens, it is hoped that PKH can be implement well, because the success of government work programs depends on community participation as program implementers.